Aggregation‐Induced Emission: A Challenge for Computational Chemistry Taking TPA‐BMO as an Example. Issue 17 (12th July 2021) - de Thieulloy, Laure; Le Bras, Laura; Zumer, Benoît; Sanz García, Juan; Lemarchand, Claire; Pineau, Nicolas; Adamo, Carlo; Perrier, Aurélie
Abstract: A multi‐environment computational approach is proposed to study the modulation of the emission behavior of the triphenylamine (Z)‐4‐benzylidene‐2‐methyloxazol‐5(4H)‐one (TPA‐BMO) molecule [Tang et al ., J. Phys. Chem. C 119, 21875 (2015)]. We aim at (1) proposing a realistic description of the molecule in several environments (solution, aggregate, polymer matrix), (2) modelling its absorption and emission properties, and (3) providing a qualitative understanding of the experimental observations by highlighting the photophysical phenomena leading to the emission modulation. To this purpose, we rely on (TD‐)DFT calculations and classical Molecular Dynamics simulations, but also on the hybrid ONIOM QM/QM' approach and the in situ chemical polymerization methodology. In low‐polar solvents, the investigation of the potential energy surfaces and the modulation of the emission quantum yield can be attributed to possible photophysical energy dissipation caused by low‐frequency vibrational modes. In the aggregate and in the polymer matrix, the emission modulation can be qualitatively interpreted in terms of the possible restriction of the intramolecular vibrations. For these two systems, our study highlights that a careful modelling of the environment is far from trivial but is fundamental to model the optical properties of the fluorophore. Abstract : Pile up : A multi‐scale and multi‐environment computational approach is proposed to investigate the modulation of the emission behavior of the triphenylamine (Z)‐4‐benzylidene‐2‐methyloxazol‐5(4H)‐one (TPA‐BMO) molecule in low‐polar solvents, within an aggregate and within a polymer matrix.